The early medieval settlement remains from Flixborough, Lincolnshire : the occupation sequence, c. AD 600-1000 - Loveluck, Christopher (Excavations at Flixborough, 2007)
The quality of the overall archaeological data contained within the settlement sequence is important for both the examination of site-specific issues, and for the investigation of wider research themes and problems, facing settlement studies in England, between AD 600 and 1050. This volume focuses on the occupation sequence.